2008
DOI: 10.1007/s10508-007-9310-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Experimentally Adopted Sexual Schemas on Vaginal Response and Subjective Sexual Arousal: A Comparison Between Women with Sexual Arousal Disorder and Sexually Healthy Women

Abstract: The present study evaluated and compared the effects of experimentally adopted sexual schemas on vaginal response, subjective sexual arousal, and affect in 17 women with Female Sexual Arousal Disorder (FSAD) and 17 sexually healthy women. Positive and negative cognitive schemas were presented to participants before viewing sexually explicit video segments. They were asked to temporarily adopt both schemas, and vaginal response, subjective sexual arousal, and affect were measured in each schema condition. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 32 publications
3
27
1
1
Order By: Relevance
“…This result is consistent with previous findings that depressive symptoms did not predict schemas in community (Kuffel & Heiman, 2006) and sexually disordered samples (Middleton et al, 2008), but stands in contrast to Meston et al's (2006) study and the larger literature linking depressive symptoms to sexual impairment. Future research is needed to clarify the relationship between depressive symptomatology and sexual self-schema as well as their connection to sexual behavior.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is consistent with previous findings that depressive symptoms did not predict schemas in community (Kuffel & Heiman, 2006) and sexually disordered samples (Middleton et al, 2008), but stands in contrast to Meston et al's (2006) study and the larger literature linking depressive symptoms to sexual impairment. Future research is needed to clarify the relationship between depressive symptomatology and sexual self-schema as well as their connection to sexual behavior.…”
Section: Discussionsupporting
confidence: 91%
“…In Meston et al's (2006) CSA survivor sample, higher depressive symptoms were associated with less positive scores on the romantic/passionate subscale after controlling for anxiety. Conversely, depressive symptoms were not associated with sexual schemas after controlling for anxiety in samples of 56 community women (Kuffel & Heiman, 2006) or 17 women with sexual arousal disorder (Middleton, Kuffel, & Heiman, 2008). Thus, it appears that for women with a history of interpersonal assault, increased depressive symptoms may be associated with more negative sexual self-schemas.…”
mentioning
confidence: 84%
“…This result suggests that treatment of sexual problems may be improved by not only amelioration of negative expectations and distracting NETs, but the fostering of a positive orientation towards sexual activity. For instance, recent research has shown that inducing a positive schema significantly facilitated sexual arousal in women (Kuffel & Heiman, 2006;Middleton et al, 2008). Nevertheless, directionality of these factors cannot be determined from the current study and it is also possible that reducing sexual problems would increase positive affect, reduce sexual anxiety, and the frequency of NETs.…”
Section: Discussionmentioning
confidence: 71%
“…However, given that Barlow's model was proposed to account for performance concerns in men with erectile dysfunctions, and only recently has been extended to pertain to female sexual problems (Wiegel et al, 2007), relatively few studies have evaluated these factors in other forms of sexual dysfunction or in women. Nevertheless, experimental research with women has similarly shown that adopting negative sexual schemas (Kuffel & Heiman, 2006;Middleton, Kuffel, & Heiman, 2008) and distraction from erotic aspects of a sexual situation (e.g., Elliott & O'Donohue, 1997) reduced sexual arousal in women as it does in men (Geer & Fuhr, 1976). Together this research supports Barlow's contention that sexual arousal problems in women and men are likely a complex interaction of feedback loops involving negative sexual expectancies, negative affect, and greater attentional focus on performance-related features of a sexual situation (Wiegel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Negative cognitions and attitudes about sexuality may make women more vulnerable to experiencing arousal difficulties (Middleton, Kuffel, & Heiman, 2008;Nobre & Pinto-Gouviea, 2006. Cognitive distraction from erotic cues, sometimes induced by self-consciousness about body image (Dove & Wiederman, 2000), can also reduce sexual arousal.…”
Section: Factors Underlying Fsadmentioning
confidence: 99%